2020
DOI: 10.21053/ceo.2019.00388
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Prognostic Factors for the Parotid Cancer Treated With Surgery and Postoperative Radiotherapy

Abstract: Objectives. To investigate the prognostic factors and treatment outcomes of primary parotid carcinoma treated with surgery and postoperative radiotherapy (PORT).Methods. We reviewed retrospectively 57 patients with primary parotid carcinoma who were treated with surgery and PORT between 2005 and 2014. Superficial parotidectomy was performed in 19 patients, total parotidectomy in 10 patients, and total parotidectomy with lymph node dissection in 28 patients PORT on the tumor bed was performed in 41 patients, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 29 publications
2
23
1
1
Order By: Relevance
“…Our study demonstrated that the 5‐year OS and DFS among patients with PGC who underwent curative treatment were 73.1% and 62.8%, respectively. These rates were previously reported to be 46% to 82.9% 1,3‐6,21–24 and 60.2% to 74.4%, 3–5,25 respectively; our results are consistent with those of previous studies, given that the treatment protocol at our institution is based on the National Comprehensive Cancer Network guidelines for head and neck cancers 26…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study demonstrated that the 5‐year OS and DFS among patients with PGC who underwent curative treatment were 73.1% and 62.8%, respectively. These rates were previously reported to be 46% to 82.9% 1,3‐6,21–24 and 60.2% to 74.4%, 3–5,25 respectively; our results are consistent with those of previous studies, given that the treatment protocol at our institution is based on the National Comprehensive Cancer Network guidelines for head and neck cancers 26…”
Section: Discussionsupporting
confidence: 93%
“…Owing to its low incidence and histological diversity, the prognoses of patients with PGC remain unclear. Previous studies have revealed that prognostic factors for such patients include age, 3 TNM classification, 1,4 preoperative facial paralysis, 5 high‐risk histology, 6 perineural invasion, 5 lymphovascular invasion, 4 and surgical margin 5 …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the anatomy of gland innervation may, in part, explain the effects of radiation therapy on autonomic nerves. Because the cell bodies of parasympathetic ganglia are located within SGs, they may be more affected by radiation therapy, whereas sympathetic nerve cell bodies are located in the superior cervical ganglion, and are thus distant from the site of radiation therapy [19][20][21][22]. The maintenance of a progenitor cell population as a reservoir of undifferentiated cells is required for the development and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery, radiation with or without chemotherapy and their combination are recommended treatment options for locoregional relapse [12]. Retrospective studies showed that comprehensive treatment strategies can reduce the local recurrence rate by 5-40% [13,14] and postoperative radiotherapy (PORT) was recommended for patients with prognostic risk factors [15,16]. However, the e cacy of adjuvant radiotherapy on speci c patients of parotid adenocarcinoma needs further determined to better screen patients bene tting from PORT, which will be conducive to avoid the additional damage caused by overtreatment.…”
Section: Introductionmentioning
confidence: 99%